2022
DOI: 10.1002/cpdd.1162
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Oral NLRP3 Inflammasome Inhibitor ZYIL1: First‐in‐Human Phase 1 Studies (Single Ascending Dose and Multiple Ascending Dose)

Abstract: ZYIL1 is a nucleotide‐binding oligomerization domain, leucine rich repeat and pyrin domain‐containing 3 (NLRP3) inflammasome inhibitor, which prevents NLRP3‐induced apoptosis‐associated speck‐like protein containing a caspase activation and recruitment domain oligomerization, thus inhibiting NLRP3 inflammasome pathway. We investigated the safety, tolerability, pharmacokinetic, and pharmacodynamic profiles of ZYIL1 after single and multiple doses in healthy subjects. The subjects aged 18–55 years were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…However, considering that both MCC950 and GDC-2394 were halted due to liver toxicity issues, researchers should diligently monitor the liver toxicity in clinical trials of candidate drugs built upon the MCC950 scaffold. While Zydus stated that ZYIL1 showed no abnormalities in renal and liver function tests during the Phase IIa trial, the relatively short dosing period (50 mg twice daily for 7 days) 41 calls for caution in drawing a definitive conclusion regarding its lack of hepatotoxicity. In addition, it is critical to identify and address the underlying mechanisms of liver toxicity associated with these drugs in order to develop effective strategies for mitigating such adverse effects.…”
Section: Exploration Of 2-furan Isopropanol Moietymentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering that both MCC950 and GDC-2394 were halted due to liver toxicity issues, researchers should diligently monitor the liver toxicity in clinical trials of candidate drugs built upon the MCC950 scaffold. While Zydus stated that ZYIL1 showed no abnormalities in renal and liver function tests during the Phase IIa trial, the relatively short dosing period (50 mg twice daily for 7 days) 41 calls for caution in drawing a definitive conclusion regarding its lack of hepatotoxicity. In addition, it is critical to identify and address the underlying mechanisms of liver toxicity associated with these drugs in order to develop effective strategies for mitigating such adverse effects.…”
Section: Exploration Of 2-furan Isopropanol Moietymentioning
confidence: 99%
“…In vitro studies have shown that MCC950 could readily produce oxidative metabolites when exposed to liver microsomal enzymes, thereby leading to the generation of hydroxylated active metabolites . Similarly, in vivo metabolic data for ZYIL1 also suggested that the cyclopentane moiety is susceptible to hydroxylation or dehydrogenation . Therefore, the introduction of modifications to the tricyclic motif not only enhances structural diversity but also holds the potential to improve metabolic stability, which makes it a promising avenue for further exploration.…”
Section: Structural Modification Based On the Compound Mcc950mentioning
confidence: 99%
“…5,18,19 Therefore, the reconfiguration of MCC950, in particular, the replacement of the furan moiety to improve its drug suitability, is highly necessary. As a matter of fact, there are many drugs that have been reconfigured in this way, of which ZYIL1, 20 IFM-2427, 21 Inzomelid, 22 and RG-6418 23 have entered the clinical phase, which suggests that optimizing the furan moiety could therefore be a promising strategy for obtaining a potent NLRP3 inhibitor (Figure 1). In this study, we designed and synthesized a series of NLRP3 inflammasome inhibitors, building upon the foundation of MCC950 and focusing on the optimization of its furan moiety in order to improve druggability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although a specific reason for drug-induced liver injury (DILI) was never disclosed, Dr. Latz and colleagues suggest that the metabolically reactive furan, along with the very high clinical dose of 1200 mg per day, could be two potential factors underlying the observed DILI. ,, Therefore, the reconfiguration of MCC950, in particular, the replacement of the furan moiety to improve its drug suitability, is highly necessary. As a matter of fact, there are many drugs that have been reconfigured in this way, of which ZYIL1, IFM-2427, Inzomelid, and RG-6418 have entered the clinical phase, which suggests that optimizing the furan moiety could therefore be a promising strategy for obtaining a potent NLRP3 inhibitor (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent detailed research regarding the mechanism of action revealed that CP-456,773 (CRID3, MCC950), composed of diarylsulfonyl urea, inhibited activation of the NLRP3 inflammasome followed by reduced IL-1β in pharmacological in vitro experiments and in vivo model studies in mice. , After those pioneering research efforts were reported, development of various NLRP3 inflammasome inhibitors have been enthusiastically investigated. In Figure , the chemical structures of representative compounds that act as NLRP3 inhibitors are illustrated. In this report, we describe our medicinal chemistry efforts to identify novel NLRP3 inflammasome inhibitors and their therapeutic potential for glomerulonephritis.…”
mentioning
confidence: 99%